Combination Intervention Cognitive Behavior Therapy and Consultation Liaison Psychiatry Nursing on Adolescents to Decrease Anxiety Problem - Pandeirot, Nancye; Husni, Amin; Ratna Sawitri, Dian (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2023)
Introduction: The existence of demands that occur simultaneously causes some adolescents to be unable to adapt properly, especially the condition of adolescents who experience changeable emotions, are unstable, easily stressed, feel anxious, depressed, and feel helpless. Combination Intervention Cognitive Behavior Therapy And Consultation Liaison Psychiatry Nursing (CICBTnCLPN) is a form of psychotherapy that can be used for adolescent emotional problems. The purpose of this study is to provide that a combination of CBT and CLPN interventions can further reduce adolescent anxiety levels, compared to only CBT interventions. Method: The research type of quasi-experimental research, with a pretest-posttest control group design. The research sample was 64  adolescents with anxiety problems at Surabaya with techniques systematic sampling. The independent variable was combination of CBT and CLPN interventions (CICBTnCLPN), the dependent variable was the level of anxiety. Data collection used an instrument in the form of a TIMAS. The data have been analyzed by Independent T Test.                Result: There was a significant difference in the decrease in adolescent anxiety levels between group that received the combination of CBT and CLPN intervention and  group that only received CBT intervention. The statistical test results showed a significant value or p-value of 0.002 or P <0.05. It can be concluded that the combination intervention of CBT and CPLN is better at reducing anxiety levels than using only the CBT method. Conclusion: CICBTnCLPN can further reduce adolescent anxiety levels. By changing the form of thought and the resulting consequences, the intensity of the subject's anxiety decreases.